Identifying the critical factors of environmental management and developing their performance measures. - Yeo, Soo Wee. (2008)
This study identified seven critical success factors of environmental management for businesses and developed performance measures for each critical factor. The seven critical factors are: Top Management Commitment to Environmental Management, Total Involvement of Employees, Training, Green Product/Process Design, Supplier Management, Measurement and Information Management. Using manufacturing companies in Singapore as target respondents, results from the survey support the seven critical success factors.